Diocese de Crateús: escrita popular, leitura radical e resistência – (1964-1989) - Carmo, Sávio Mendes do (2024)
This research aims to explore the peasant culture in the Diocese of Crateús, focusing on the role of popular reading and writing in shaping a culture of resistance. The study discusses the establishment of the Diocese in 1964 by Bishop Dom Antônio Batista Fragoso and his vision to build a Church where grassroots sectors were the main agents in creating a popular pastoral project. We examine how this initiative influenced the formation of an ecclesial movement and contributed to the emergence of social organizations and movements. We also analyze how such an ambitious project provoked strong reactions from various social, economic, and political groups in the region. However, we emphasize the capacity for resistance developed by these individuals, who created diverse strategies for their struggles. The acquisition of literacy plays a crucial role in these conflicts, highlighting not only the cultural power of reading and writing but also their generative and organizing influence in resistance mobilizations. We focus on the method of radicalizing this literacy through pamphlets, booklets, notebooks, and pastoral aids, later expressed in poetry, cordel literature, and letters written by the workers. Our objective was to analyze the culture of resistance as a practice built in everyday life, conversation, faith, reading, writing, and reflection among the people of the sertões of Crateús and Inhamuns